2022
DOI: 10.1186/s12913-022-08008-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing person-centeredness in psychosis inpatient care: staff experiences from the Person-Centered Psychosis Care (PCPC) project

Abstract: Background Interventions to increase person-centeredness in hospital care for persons with psychotic illness are needed. Changing care delivery is however a complex venture, requiring staff to reconsider their mindsets and ways of working. A multidisciplinary educational intervention for hospital staff at four wards was launched to increase person-centeredness in the care of patients with schizophrenia and similar psychoses. This study aims to explore staff experiences of working to increase pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…This kind of individualized care would then be employed to maintain security, effect adherence, and to some extent, achieve some degree of patient emancipation albeit with security prerogatives of the surrounding society setting limits to the scope of adjustments that HCPs can make. This possibility is consistent with the conclusions of Allerby et al [ 27 ], whose study revealed that staff do not perceive their patient’s psychotic symptoms or involuntary setting to be a hurdle for PCC implementation.…”
Section: Discussionsupporting
confidence: 92%
“…This kind of individualized care would then be employed to maintain security, effect adherence, and to some extent, achieve some degree of patient emancipation albeit with security prerogatives of the surrounding society setting limits to the scope of adjustments that HCPs can make. This possibility is consistent with the conclusions of Allerby et al [ 27 ], whose study revealed that staff do not perceive their patient’s psychotic symptoms or involuntary setting to be a hurdle for PCC implementation.…”
Section: Discussionsupporting
confidence: 92%
“…32 Sufficient time was not only needed for the treatment planning session/s with service users but also for clinicians beforehand to learn a new tool and approach, as well as for collaboration with colleagues when needed. 33,36,37,45,63 Service users were acutely aware of time constraints on practitioners and it affected how some experienced the process. 59 "like, just getting the laundry done is a hassle, so for me to take someone, sort of, offline and concentrate on me One of the larger studies found that only a very small proportion of people felt that they were too unwell to complete a facilitated plan (9/285 = 3%) 64 and another similarly reported that of 128 observations, most service users were found (by clinicians) to be interested in and able to understand the shared, medical decision-making process.…”
Section: Process Barriersmentioning
confidence: 99%
“…42 Cultural and language differences could also be a barrier, from the clinician's perspective, that sometimes hindered the shared decision-making experience. 33,49,52 Involving different parties (including colleagues and family members) in the planning process was another barrier that has been reported as being difficult, or at least perceived as difficult. 31,36,65,69 Additional barriers to plan completion may also be experienced by (a) younger people, in one study those under median age 42 years were less likely to complete a plan compared with their older counterparts 53 ; (b) people discharged, relocating away or not receiving care from services where such planning occurred 32,80 ; (c) people who were experiencing homelessness and poverty; 42,69 and (d) although less education was shown to be associated with higher rates of plan completion, 81 illiteracy was viewed by both service users and providers as a potentially significant barrier to planning involvement and completion, and may influence whether clinicians offer such planning opportunities.…”
Section: Process Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC has been introduced in a variety of care contexts, including inpatient care, rehabilitation, outpatient care, school settings and primary care 10 in patient groups with acute psychosis, acute coronary heart disease, hypertension, rheumatism, heart failure, hip fractures, long-term pain and nursing home residents. 10,11…”
Section: Pcc Only Work In Certain Healthcare Settingsmentioning
confidence: 99%